PTH-019 Does Rectal Diclofenac Reduce Post ERCP Pancreatitis in The UK?. (17th August 2016) - Sheiybani, G; Toolan, M; Brydon, P; Linehan, J; Farrant, M; Colleypriest, B
Abstract : Introduction: Post ERCP pancreatitis(PEP) occurs in up to 10% of unselected cases and carries significant morbidity. PEP is significantly higher in certain patient groups, for example females, young age, Sphincter of Oddi dysfunction, previous pancreatitis and following pancreatic duct cannulation. There is a growing body of evidence that NSAIDS should be used in PEP prophylaxis but use is still uncommon in the UK. The 2010 European Society for Gastrointestinal Endoscopy Guidelines on PEP recommends routine use of rectal NSAIDs in all patients. There is only one published RCT from the UK demonstrating the efficacy of NSAIDS in reducing PEP. Rectal diclofenac was introduced into ERCP practice at the RUH in two phases. Firstly, a selective use in patients determined to be at high risk as determined by criteria above. Secondly diclofenac was used routinely in all patients without contraindication. Methods: A retrospective analysis of 5 years ERCP data was performed using readmission data, blood results, radiology reports and discharge summaries to identify patients with PEP from August 2010 – December 2015. The administration of rectal diclofenac post procedure was recorded from the endoscopy reporting system. Fisher's exact test was used to statistically analyse categorical data. Results: 1318 ERCPs were performed by 4 endoscopists during the study period with 66 (5.0%) cases of pancreatitis. 445 ERCPs were performed prior to the introduction of NSAID use during which time there were 35 (7.9%) episodes of PEP. During the selective period of NSAID use (only used if patient deemed high risk by endoscopist) 539 ERCPs were performed and 72 (13.4%) patients received NSAIDS. 17 (3.2%) developed PEP. 334 ERCPs were performed when NSAIDS were given to all patients without contraindication. 289 (86.5%) of patients received rectal diclofenac and 13 (3.9%) developed pancreatitis. There is a statistically significant decrease in PEP comparing the groups of patients receiving NSAIDS selectively (p = 0.0009) or routinely (p = 0.0172) when compared with none. There is no difference between the selective and routine group (p = 0.571). Conclusion: The use of rectal diclofenac post ERCP decreases the rate of PEP when used in a selective or routine protocol. Despite a growing body of evidence for NSAIDS use routine administration is used by the minority of endoscopists in the UK. The evidence for use of NSAIDS in PEP is heterogeneous a number of factors including diagnostic criteria for pancreatitis, type and route of NSAID and selective high risk or routine use. We believe that this heterogeneity and lack of UK evidence accounts for the slow uptake of NSAIDS for PEP. Our data demonstrates that the introduction of a selective or routine use of NSAIDS for PEP in a DGH significantly decreases the risk of pancreatitis (RR 43.7%). Disclosure of Interest: None Declared